Analysis of the Added Value of the Tofu Tempe Industry in Lambusa Village, Konda District, South Konawe Regency Using the Hayami Method - Muhammad Tisakti; Muhammad Syukri; Sakir Sakir (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2021)
This study aims to determine the process of processing tofu and tempeh in the Home Industry in Lambusa Village, Konda District, South Konawe Regency. The research was carried out in October 2020 to completion at the Elsa Jaya Tofu Tempe Home Industry in Lambusa Village, Konda District, South Konawe Regency, Southeast Sulawesi Province. Respondents in this study were Tofu Tempe entrepreneur Elsa Jaya because those who know more about tofu and tempeh production are the business owners themselves. This study's data collection techniques were observation, interviews (interviews), and recording. The study results indicate that the processing of tofu and tempeh at the Home Industry of Tofu and Tempe Elsa Jaya has complied with SNI 01-3707-2013. The profit from tofu processing in the Elsa Jaya home industry in Lambusa Village, Konda District, South Konawe Regency is Rp. 1,618,000, with a profit rate of 99.81%. In comparison, the profit on tempe processing is Rp. 460,800, with a profit rate of 74.20%.